Communication—Preparation of a Porous β-Cu3V2O8 Film for Photoelectrochemical Water Oxidation. Issue 6 (4th June 2021) - Tang, Ding; Zhong, Shuiping
Abstract : The combination of narrow band gaps and notable stabilities against photoelectrochemical corrosion brings copper vanadates into the forefront of emerging photoanodes. Herein, we report a feasible approach to fabricate β -Cu3 V2 O8 thin film with a porous structure directly on indium-doped tin oxide (ITO) substrate for photoelectrochemical water oxidation. The porous β -Cu3 V2 O8 photoanode exhibits a photocurrent density of 220 μ A cm −2 at 1.55 V vs RHE (reversible hydrogen electrode) in pH 9.2 borate buffer electrolyte under simulated solar irradiation. The present work could provide a base for further development of porous β -Cu3 V2 O8 as a solar fuels photoanode.